Exploring Oral Polymorphous Adenocarcinoma: Clinical Characteristics, Diagnosis, and Treatment Outcomes. A Case Report - Christina Charisi; Vasileios Zisis; Petros Papadopoulos; Konstantinos Poulopoulos; Nikolaos Kyriakou; Athanasios Poulopoulos (Reports, 2025)
Background and clinical significance: Polymorphous adenocarcinoma of the oral cavity is predominantly located in the palate. It is characterized by a slow rate of growth and thus may be misdiagnosed as a benign tumor. Its histology is intricate with other salivary malignancies, thus necessitating specific immunohistochemical stains. Our case report illustrates an adenocarcinoma localized in the palate of a 61-year-old female patient. Case presentation: The patient came to the postgraduate clinic of Oral Medicine and Pathology, Department of Oral Medicine and Pathology, School of Dentistry, Faculty of Health Sciences, Aristotle University of Thessaloniki, Greece and provided written informed consent for the subsequent examination. The patient complained about the presence of a mass on the palate, which was otherwise asymptomatic, without being able to pinpoint when the tumor initially emerged. The lesion was biopsied and the histology suggested the immunophenotype p63+/p40- which constitutes an important diagnostic clue for polymorphous adenocarcinoma. The patient was referred to the Department of Oral and Maxillofacial Surgery. Conclusions: The standard therapeutic approach primarily involves surgical excision. The goal is to achieve optimal patient outcome while minimizing unnecessary morbidity. As surgical techniques and understanding of the disease continue to advance, it is crucial for healthcare providers to stay informed and integrate these developments into practice to improve treatment outcomes for patients.